2021
DOI: 10.1002/aws2.1250
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical equilibrium lead(II) solubility revisited: Open source code and practical relationships

Abstract: A theoretical equilibrium lead(II) (Pb(II)) solubility model coded in Fortran (LEADSOL) was updated and implemented in open source R code, verified against LEADSOL output, and used to simulate theoretical equilibrium total soluble Pb(II) (TOTSOLPb) concentrations under a variety of practical scenarios. The developed R code file (app.R) is publicly available for download at GitHub (https://github.com/USEPA/TELSS) along with instructions to run the R code locally, allowing the user to explore Pb(II) solubility b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The results from both demonstration studies indicate a point of diminishing returns at higher orthophosphate doses. These findings are consistent with lead solubility models shown in Figure 6 as well as other studies that have found diminishing returns for especially above 1.5-2 mg/L as PO 4 in the pH 7-8 range (Bradley & Horscroft, 2018;Cardew, 2009;Schock, 1980;Schock et al, 1996;Schock & Gardels, 1983;Wahman et al, 2021).…”
Section: Comparison Of Orthophosphate Treatment In Coupon and Pipe Ra...supporting
confidence: 92%
See 2 more Smart Citations
“…The results from both demonstration studies indicate a point of diminishing returns at higher orthophosphate doses. These findings are consistent with lead solubility models shown in Figure 6 as well as other studies that have found diminishing returns for especially above 1.5-2 mg/L as PO 4 in the pH 7-8 range (Bradley & Horscroft, 2018;Cardew, 2009;Schock, 1980;Schock et al, 1996;Schock & Gardels, 1983;Wahman et al, 2021).…”
Section: Comparison Of Orthophosphate Treatment In Coupon and Pipe Ra...supporting
confidence: 92%
“…The ideal pH range for orthophosphate effectiveness for controlling lead corrosion is between 7.2 and 7.8 (Schock, 1989; Schock et al, 1996), similar to the finished water quality in the Denver Water system before March 2020. Orthophosphate also tends to be more effective at controlling lead corrosion in low alkalinity waters (Schock, 1989; Wahman et al, 2021). Typical orthophosphate doses are between 0.5 and 3 mg/L as PO 4 (Vik et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Models which account for the diverse, interconnected mechanisms of lead release, including bulk thermodynamic and kinetic factors, the effects of environmental changes (e.g., temperature and increased salinity from rising sea levels), additives, disturbances in pipelines, and flow rates, are lacking. In particular, the ultimate structure and mechanisms by which corrosion inhibitors form solid scales in pipes that limit lead (II) release are not fully understood. ,, For example, it has been shown that the addition of orthophosphate as a corrosion inhibitor causes the formation of scales dominated by hydroxylpyromorphite and Pb 3 (PO 4 ) 2 . ,, Although studies have directly observed lead carbonate scales to form on pipes expected under operating conditions, other data on lead phosphate scales are unable to identify such scales despite current models predicting their stability. , We note that characterizing the growth of scales is challenging in part because of limited spectral ranges for Raman spectroscopy, inadequate solution control, little initial starting scale monitoring, and the ex situ testing nature due to removal and recovery of scales on pipes for laboratory characterization. These limitations necessitate the integration of literature covering multiple experimental techniques here and elsewhere to best support solid lead phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the U.S. Environmental Protection Agency (USEPA), it was standard protocol throughout the 20th century to use lead pipes for commercial and domestic water supplies. These pipelines were damaged because of lead concentrations in water, increasing concentrations of organic, and inorganic contaminants with various microorganisms, and the duration of water stay in these pipelines (Wahman, D. G., et al, 2021;Enning D, and Garrelfs J., 2014). All these happening are because of physical, biological, and chemical reactions in water throughout its passage from the water supply system to the consumer as shown in figure 1.…”
Section: Occurrence Of Contamination In Water Suppliesmentioning
confidence: 99%